JIRA Agile essentials : bring the power of Agile to Atlassian JIRA and run your projects efficiently with Scrum and Kanban /: bring the power of Agile to Atlassian JIRA and run your projects efficiently with Scrum and Kanban. (2015) - Li, Patrick
No abstract available